Interferometry applications in all-optical communications networks - Dionísio, Rogério (2017)
Throughout the years, the expanded search and flow of information led to an expansion of traffic intensity in today’s optical communication systems. Coherent communications, using the amplitude and phase of the optical wave, resurface as one of the transmission methods to increase the effective bandwidth of optical channels. In this framework, this chapter presents a study on all-optical format conversion of modulated signals, using exclusively interferometric techniques through wavelength conversion, based on Mach-Zehnder interferometers with semiconductor optical amplifiers (MZI-SOA). This technique, when applied in interconnection nodes between optical networks with different bit rates and modulation formats, allows a better efficiency and scalability of the network. The chapter presents an experimental characterization of the static and dynamic properties of the MZI-SOA and explores all-optical techniques for the conversion from amplitude modulation to phase modulation. Finally, it briefly presents the potential of MZI-SOAs for the conversion of amplitude signals to more advanced modulation formats, such as quadrature phase shift keying (QPSK) and quadrature amplitude modulation (QAM) signals.